Big data, sport, and the digital divide: Theorizing how athletes might respond to big data monitoring - Baerg, A. (Journal of Sport and Social Issues, 2017)
This article considers the relationship between Big Data and the athlete. Where Beer and Hutchins have focused on Big Data and sport, this article concentrates on the athlete`s potential response to Big Data monitoring. Drawing on the work of Andrejevic, and Kennedy and Moss, the project speaks to the Big Data-athlete relation through the theoretical framework of the digital divide. It describes Big Data and its relation to the digital divide before tracing out how athletes might respond to Big Data monitoring by presenting concerns about privacy and/or embracing a quantified self. Considering these responses provides a starting point for further work on how athletes should treat Big Data and its implications for sport.